The Routledge history of queer America
1 online resource (xvi, 388 pages)
Keywords: "The Routledge History of Queer America presents the first comprehensive synthesis of the rapidly developing field of lesbian, gay, bisexual, transgender and queer US history. Featuring nearly thirty chapters on essential subjects and themes from colonial times through the present, this collection covers topics including: Rural vs. urban queer historiesGender and sexual diversity in early American historyIntersectionality, exploring queerness in association with issues of race and classQueerness and American capitalismThe rise of queer histories, archives, and collective memoryTransnationalism and queer historyGathering authorities in the field to define the ways in which sexual and gender diversity have contributed to the dynamics of American society, culture and nation, The Routledge History of Queer America is the finest available overview of the rich history of queer experience in US history. "--Provided by publisher.